Pengaruh Kadar Air dan Enerji Pemadatan terhadap Hydraulic Conductivity Lempung yang Dipadatkan - Arifin, Yulian Firmana (INFO-TEKNIK, 2001)
This research will observe the effect of water content and compaction effort to the hydraulic conductivity of Karang Pilang Surabaya Clay used for clay liner of municipal waste disposal area.In this research, clay was taken from Karang Pilang, Surabaya.  Clay was compacted with Standard Proctor and Modified Proctor Tests.  From each of them,five sample were prepared at different water content (wc apt),2 (two) at wc<wc apt (wet side).  In order to obtain the hydraulic conductivity (k) of the clay liner, falling head test using 0.005 N CaSO4 was carried out.The result showed that hydraulic conductivity of compacted clays with the increasw of water content until ± 4 % over wopt.  The hydraulic conductivity of compacted at wit side is lower than the clay compacted at dry side.  The increase of compaction effort increasing density of clay results in the increase of hydraulic condctivity significantly.  For different clays, higher density does not assurance lower hydraulic conductivity, the hydraulic conductivity is also influenced by plasticity of clays.